EVALUATING THE EFFECTIVENESS OF HEPATITIS AND HIV PREVENTION PRACTICES AMONG DIALYSIS PATIENTS (Journal of Medical & Health Sciences Review, 2025)
Background: Hepatitis B, Hepatitis C, and HIV infections are more likely to occur in patients with chronic kidney disease (CKD), who must get dialysis. Outbreaks and diseases continue despite preventative efforts, highlighting the need for efficient prevention techniques.Objective: To evaluate the effectiveness of Hepatitis and HIV prevention practices in dialysis settings and identify gaps for evidence-based improvements.Methodology: This multicenter cross-sectional study was conducted between January and December 2023, utilizing data collected from various hospitals across Pakistan, including prominent medical institutions in Peshawar, Bahawalpur, Kohat, and Sialkot. The data collection methods comprised retrospective record reviews, direct observations, and structured interviews involving 218 dialysis patients and 50 healthcare providers. Statistical analysis was performed using SPSS software. Chi-square tests were employed to assess the relationships between infection rates, vaccination coverage, and infection control strategies, with statistical significance set at a p-value of less than 0.05.Results: The study's p-values were above 0.05, indicating that there were no statistically significant correlations between infection rates and infection control measures (hand hygiene: 14.37%, p=0.15; sterilization protocols: 14.12%, p=0.16; patient isolation: 12.63%, p=0.10; universal precautions: 13.87%, p=0.12). Nonetheless, there were notable correlations between vaccination coverage and infection rates, with 8.89% for Hepatitis B (p=0.006) and 10.00% for Hepatitis C (p=0.005).Conclusion: Hepatitis and HIV infections among dialysis patients were shown to be significantly decreased by vaccination coverage, but infection control strategies showed only patchy results. The results emphasize the need of focused actions aimed at raising immunization rates in order to strengthen efforts to avoid infections.